Studi Eksperimen Kinerja Sensor Water Level dan Sensor Raindrop melalui Pengukuran Tegangan Analog - Sucaga, Siti Fadilah; Zahra, Andi Muthia Ainun; Estu Broto, Prasepvianto (SAINFIS: Jurnal Sains Fisika, 2025)
The water level sensor and raindrop sensor are essential components in water monitoring systems that require performance evaluation to ensure measurement accuracy. This study aims to analyze the analog output in the form of voltage from both sensors and calculate the error rate in their measurements. The method involves testing the water level sensor at varying water heights, ranging from 0.4 cm to 4 cm, and testing the raindrop sensor with variations in water droplet volume. The experiments were conducted using tools such as a digital multimeter, power supply, ruler, tissue, and other supporting devices. The measurement results show that the water level sensor has a relatively low error rate, ranging from 0.166965% to 7.259148%. Meanwhile, the raindrop sensor produces voltage variations between 1.6 V and 4.8 V, with an error rate ranging from 1.74679% to 14.89631%. Based on these findings, it can be concluded that the water level sensor demonstrates high stability for water level monitoring applications, whereas the raindrop sensor requires more precise management to improve its accuracy in detecting water droplets.